2002
DOI: 10.1007/s00134-002-1509-x
|View full text |Cite
|
Sign up to set email alerts
|

Acute haemodynamic effects of a hypertonic saline/dextran solution in stable patients with severe sepsis

Abstract: Hypertonic saline/dextran solution may improve cardiovascular performance in severe sepsis without significant side effects. The haemodynamic effect appears related mainly to a volume effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…From a clinical perspective, Hannemann et al 20 conducted the first study on the effect of small volume resuscitation in severe sepsis. Oliveira et al 21 reported that an HTS/dextran solution improved cardiovascular performance and resuscitated patients with severe sepsis through a volume effect, but may also directly improve cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, Hannemann et al 20 conducted the first study on the effect of small volume resuscitation in severe sepsis. Oliveira et al 21 reported that an HTS/dextran solution improved cardiovascular performance and resuscitated patients with severe sepsis through a volume effect, but may also directly improve cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…The use of 7.5% HTS/Dextran 70 was associated with short-lived improvement in hemodynamic status in patients with severe sepsis compared to normal saline. 64 It can also improve the oxygen delivery and cardiac output in septic shock patients. 65 Effat et al used HTS in forty critically ill patients with septic shock, where it decreases CRP levels, improves in cardiac functions, sepsis scores, use of vasopressors, decreases ICU stay, and mechanical ventilation days.…”
Section: Neurogenic Shockmentioning
confidence: 99%
“…Also, human prehydration with intravenous fluid (1.5 L of 2.5% glucose/0.45% NaCl), 1 h prior to an injection of Escherichia coli purified LPS endotoxin, may shift the resulting cytokine balance towards a more anti-inflammatory pattern, with a reduction of symptoms [ 123 ] and an outcome that is similar to the successful treatment of sepsis (i.e., life-threatening organ dysfunction caused by a dysregulated host response to infection [ 47 ] via i.v. fluid [ 124 , 125 ]). To evaluate the effects of dehydration on gastrointestinal permeability, Lambert and colleagues [ 122 ] conducted a laboratory study in which twenty trained endurance athletes (11 men, 9 women) ran three times, in a 24°C mild environment, for 60 min at 70% of maximal aerobic power.…”
Section: Factors Which Increase Intestinal Permeability and Plasmamentioning
confidence: 99%